Studies on Plant Cover of Wadi Umm El-Rakham in The Northwestern Coast of Egypt - S. TH. Ahmed, M.H.M. El-Morsy* and (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-bidi-language: AR-SA;">The present investigation was carried out to study the phytosociological characteristics of the range land in Wadi Umm El-Rakham, in Northwestern coast of Egypt during spring 2004 - fall 2005. Thirty eight plant species belong to 17 families were found in Wadi Umm El-Rakham. Eighteen species were annuals and 20 species were perennials. A total of 18 species were palatable, the rest were not. Among annulus, 11 species were palatable, whereas among perennials seven species only were palatable. Fresh and dry foliage yield, species density, frequency, herbage cover and the importance value as well as their relative values were determined in the different locations in the wadi (i.e. top, ridge and wadi bed).Ã‚Â All these traits recorded their highest value in the wadi bed location during spring season of both years 2004 and 2005. Meanwhile, the lowest values of all these traits were recorded in the wadi top location. Significant interaction was noticed among the studied factors i.e. year, location and season) in wadi bed location during spring season of both years.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â